Enhancing Micro, Small, and Medium Enterprises (MSMEs) performance through accounting knowledge, e-commerce, and network relationships - Mahmudi Mahmudi; Anggita Pamularsi (Journal of Enterprise and Development (JED), 2023)
Purpose — The growth and development of MSMEs are increasing rapidly. In order to gain customers and survive in an intensely competitive and uncertain market, MSMEs should improve their knowledge and technology, have a good understanding of electronic commerce, and expand their network relationships. This research aims to analyze the influence of accounting knowledge, understanding of e-commerce, and network relationships on the performance of MSMEs.Method — This study employs a quantitative research approach, conducted through a survey. Data were acquired by distributing questionnaires to MSME owners. The sample for this study comprises 96 MSMEs in the city of Yogyakarta, Indonesia. The independent variables in this study include accounting knowledge, understanding of e-commerce, and network relationships, while the dependent variable is the performance of MSMEs. To test the proposed hypotheses, this research utilizes multiple linear regression analysis with SPSS software for data processing.Result — The results of this research show empirical evidence that accounting knowledge, the use of e-commerce, and network relationships have a positive and significant effect on the performance of MSMEs.Contribution — This research examines the roles of accounting knowledge, the use of e-commerce technology, and business networks in MSMEs. These aspects have not been widely studied by previous researchers. The study provides new insights for MSMEs to improve performance from both internal perspectives, such as accounting and e-commerce adoption, and external perspectives, such as expanding business network relationships.